STUDI PROTEKSI DOUBLE BUSBAR AKIBAT PENAMBAHAN TRANSFORMATOR DI GARDU INDUK PEMECUTAN KELOD - I Kadek Rogan Bayu Candra Dwipa; I Gede Dyana Arjana; Cok Gede Indra Partha (Jurnal SPEKTRUM, 2019)
Pemecutan Kelod Substation operated with four conductors, three transformers, one capacitor and one coupling with double busbar configuration, side by side with the Kapal and Pesanggaran substation to maintain electricity supply in Kuta, Legian, Seminyak, Denpasar City and surrounding areas. Due to increase in load in Denpasar area, PT PLN (Persero) Trans-JBJT added one transformer to improve the reliability of electricity in this substation, so Pemecutan Kelod substation operated with four transformers. To optimize the continuity of the power flow, it is necessary to analyse the relay settings on the busbar current and the appropriate protection settings as a protection system reference. In this study, the calculation of resistor stability (Rstab) of input current and output current after and before the addition of the transformer is carried out. The results of the calculation of resistor stability (Rstab) before the addition of the transformer is obtained with a total of 5.12 ?, the input current is 1030 A and the output current is 1010 A with losses of 1.9%. While the results of the calculation of resistor stability (Rstab) after the addition of the transformer is obtained with a total of 5.64 ?, the input current is 1070 A and the output current is 1060 A with losses of 0.9%. Those losses values complied with the SPLN No.1: 1987 standard for the 150 kV system.